AI-Powered Innovations in Digestive Surgery: Current Evidence and Future Perspectives - A Systematic Literature - Napitupulu, Rudi Pandapotan; Ardli, Ghaly Khaidar; Ramadhani, Muhammad Rizky; Dira, Neysa Ornella; Sari, Andini Kartika (Indonesian Health Journal, 2025)
Artificial Intelligence (AI) is transforming the field of digestive surgery, offering significant advancements in diagnostic accuracy, surgical precision, and perioperative management. Technologies such as machine learning (ML) and deep learning (DL) enhance surgical outcomes by identifying complex patterns in data, supporting real-time decision-making, and improving personalized patient care. This study aims to systematically evaluate the current applications, challenges, and future potential of AI-powered innovations in digestive surgery. A systematic literature review was conducted following PRISMA guidelines. The search utilized databases including Scopus, PubMed, Google Scholar, Crossref, and Web of Science. Keywords like "artificial intelligence," "machine learning," "digestive surgery," and "surgical AI" yielded 3,285 articles. After applying inclusion criteria, 23 studies published between 2020 and 2024 were selected for narrative synthesis. The review highlights AI's applications in endoscopic procedures, achieving diagnostic accuracy up to 98% for early-stage cancers. AI-driven systems enhance intraoperative precision, particularly in laparoscopic and robotic surgeries, reducing complication risks and improving outcomes. Moreover, AI-based predictive models support perioperative management by optimizing surgical planning and postoperative care, demonstrating improved efficiency and patient safety. AI is reshaping digestive surgery by enabling better diagnostics, personalized treatment, and improved surgical outcomes. Despite challenges like data quality and ethical concerns, the continued evolution of AI technologies holds promise for further advancements in surgical practices and education